Contributions of the Retrosplenial and Posterior Parietal Cortices to Cue-Specific and Contextual Fear Conditioning. - Keene, Christopher S.; Bucci, David J. (Behavioral Neuroscience, 2008)
The retrosplenial cortex (RSP) and the posterior parietal cortex (PPC) are the primary sources of cortical sensory input to the postrhinal cortex (POR) in rodents. Together, these areas compose a major corticohippocampal circuit that is involved in processing visuospatial information. The POR has been implicated in contextual learning and memory, consistent with the type of information presumably being processed by this region. By comparison, little is known about the role of the RSP or the PPC in contextual learning. In the present study, rats were trained either before or after surgery in a standard signaled fear conditioning task in which an auditory cue was paired with foot shock. Contextual fear and tone-specific fear were assessed in subsequent test sessions. In Experiment 1, electrolytic damage to the RSP either before or immediately after training impaired the expression of contextual fear but not tone-specific fear. In contrast, electrolytic damage to the PPC had no effect on conditional fear to the context or the tone in Experiment 2. These findings indicate that the RSP, but not the PPC, contributes to the processing of contextual information by the POR corticohippocampal processing stream. Reprinted by permission of the publisher.